In vitro effects of the asymmetric peptidomimetic 157, containing l-tartaric acid core and valine/leucine substituents, on Leishmania amazonensis promastigotes and amastigotes. (December 2019) - Santos, André L.S.; Matteoli, Filipe P.; Gonçalves, Diego S.; Seabra, Sergio H.; Romanos, Maria Teresa V.; Branquinha, Marta H.; Resende, Gabriel O.; Cotrim, Bruno A.; Aguiar, Lucia C.S.; Sangenito, Leandro S.
Abstract: The current treatments for leishmaniasis bump into several obstacles, including low efficacy, high costs, long monitoring, and several/severe side effects. Consequently, the search for promising compounds is a tangible need. Recently, we reported the anti- Leishmania amazonensis action of asymmetric peptidomimetic compounds containing tartaric acid as core, especially the157 derivative that contains valine/leucine substituents in its structure. Herein, we decipher the multiple effects of157 on the L. amazonensis physiology and on the interaction process with macrophages. The peptidomimetic157 induced significant changes on the morphometric (internal granularity reduction as judged by flow cytometer) and on the ultrastructural (round-shaped parasites, presence of plasma membrane blebs and flagellum loss as visualized by scanning electron microscopy) aspects of treated promastigotes compared to untreated ones. The alteration on the plasma membrane permeability was confirmed by the passive incorporation of propidium iodide in157 -treated promastigotes. In parallel, the low viability of promastigotes was also associated to the perturbation of mitochondrial transmembrane electric potential. These combined results demonstrated that157 induced irreversible metabolic damages that led to L. amazonensis death. The pre-treatment of promastigotes with157 inhibited the association index with macrophages in a typically dose-dependent manner. Additionally, 157 significantly reduced the number of intramacrophage amastigotes after 72 h of drug contact, presenting an IC50 value of 30.2 μM. Under our experimental conditions, 157 showed higher toxicity to promastigotes and amastigotes when compared to RAW cells, resulting in good selective indexes. Therefore, 157 can be considered as an interesting candidate for further optimization, since its synthesis is simple and cheap.